(untitled) (Community Based Medical Journal, 2025)
Patients with chronic illnesses like cancer, diabetes, and chronic pain conditions often endure prolonged physical and emotional sufferings which tend to increase their vulnerability to suicidal ideation. Despite the global rise in chronic diseases, limited research exists on their psychological impact, especially in low-resource settings like Bangladesh. A cross-sectional study was conducted in the Department of Medicine, Rajshahi Medical College, Bangladesh, between June and December of 2023, to assess the association between chronic illness (cancer, diabetes, and chronic pain) and suicidal risk in a Bangladeshi patient population. Using purposive sampling, a total of 60 patients with cancer, diabetes, or chronic pain were enrolled. Data on demographics, illness duration, severity, and suicidal risk were collected using standardized tools. Suicidal risk was assessed using the Beck Scale for Suicide Ideation (BSS), and illness severity was measured using disease-specific scales. Logistic regression was used the see the association. Among participants, 35% had diabetes mellitus, 30% had cancer, and 35% had chronic pain conditions. Suicidal risk was significantly higher in cancer (44.4%) and chronic pain (38.1%) patients compared to diabetic patients (23.8%). Longer duration of illness (>5 years) was strongly associated with increased suicidal risk (p<0.05). Logistic regression identified cancer (OR=2.8, 95% CI: 1.2–6.5) and chronic pain (OR=2.5, 95% CI: 1.1–5.7) as independent predictors of suicidal risk. Our data suggests that chronic illnesses, particularly cancer and chronic pain, significantly increases suicidal risk. Early psychological screening and integrated mental health care are essential to mitigate suicidal ideation and improve outcomes in this vulnerable population, especially in resource-limited settings like Bangladesh. CBMJ 2025 July: vol. 14 no. 02 P:52-56